2011
DOI: 10.1002/ppul.21536
|View full text |Cite
|
Sign up to set email alerts
|

Hospital readmissions for newly discharged pediatric home mechanical ventilation patients

Abstract: Summary Background Ventilator-dependent children have complex chronic conditions that put them at risk for acute illness and repeated hospitalizations. Objectives To determine the 12-month incidence of and risk factors for non-elective readmission in children with chronic respiratory failure (CRF) after initiation on home mechanical ventilation (HMV) via tracheostomy. Methods A retrospective cohort study of 109 HMV patients initiated and followed at an university-affiliated children’s hospital between 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
116
3
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(131 citation statements)
references
References 13 publications
6
116
3
6
Order By: Relevance
“…The rehospitalization rate was significantly higher before decannulation; the most frequent reason for rehospitalization was respiratory related, as previously described. 35,36 Although no other studies have addressed the rehospitalization rates for children with tracheostomy, before and after decannulation, several have found that children who are ventilator dependent at home have a higher risk of rehospitalization than other children. 11,12,[36][37][38][39] The decrease in readmission rate after decannulation may be secondary to removal of the tracheostomy, improvement in BPD, or both.…”
Section: Discussionmentioning
confidence: 99%
“…The rehospitalization rate was significantly higher before decannulation; the most frequent reason for rehospitalization was respiratory related, as previously described. 35,36 Although no other studies have addressed the rehospitalization rates for children with tracheostomy, before and after decannulation, several have found that children who are ventilator dependent at home have a higher risk of rehospitalization than other children. 11,12,[36][37][38][39] The decrease in readmission rate after decannulation may be secondary to removal of the tracheostomy, improvement in BPD, or both.…”
Section: Discussionmentioning
confidence: 99%
“…Within this highest-utilizing group (ie, $4 rehospitalizations), technology complications were present in 8.7% of all admissions. Kun et al 30 found that tracheostomy decannulation or obstruction and tracheitis were in 12% and 17% of readmissions in the year after discharge with home mechanical ventilation, respectively. Device complications were present in 8% of a randomly selected sample of 15-day readmissions of children with chronic illnesses from another center.…”
Section: Medical Technology Device Complicationsmentioning
confidence: 99%
“…1 For children discharged from subacute care and readmitted to acute care within 30 days, ventilator dependence was one of many factors associated with readmission. 11 Kun et al, 10 however, found no statistically signifi cant associations between demographic and clinical data with nonelective readmissions to acute care from home for children dependent on mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 For children newly dependent on invasive mechanical ventilation and discharged from the hospital, the 12-month incidence of nonelective readmission has been reported at 40%. 10 This is the fi rst study examining readmission to acute care from a postacute care hospital. A recent study identifying children with chronic complex conditions reported a 19% incidence of readmission to the referring acute care hospital within 30 days of a subacute hospital discharge.…”
Section: Discussionmentioning
confidence: 99%